Protective Role of Carbonic Anhydrases III and VII in Cellular Defense Mechanisms upon Redox Unbalance. (5th August 2018) - Di Fiore, Anna; Monti, Daria M.; Scaloni, Andrea; De Simone, Giuseppina; Monti, Simona M.
Abstract : Under oxidative stress conditions, several constitutive cellular defense systems are activated, which involve both enzymatic systems and molecules with antioxidant properties such as glutathione and vitamins. In addition, proteins containing reactive sulfhydryl groups may eventually undergo reversible redox modifications whose products act as protective shields able to avoid further permanent molecular oxidative damage either in stressful conditions or under pathological circumstances. After the recovery of normal redox conditions, the reduced state of protein sulfhydryl groups is restored. In this context, carbonic anhydrases (CAs) III and VII, which are human metalloenzymes catalyzing the reversible hydration of carbon dioxide to bicarbonate and proton, have been identified to play an antioxidant role in cells where oxidative damage occurs. Both proteins are mainly localized in tissues characterized by a high rate of oxygen consumption, and contain on their molecular surface two reactive cysteine residues eventually undergoing S-glutathionylation. Here, we will provide an overview on the molecular and functional features of these proteins highlighting their implications into molecular processes occurring during oxidative stress conditions.